LRP8 is an entry receptor for tick-borne encephalitis viruses - Pengfei Li; Sean Hui; Zhenlu Chong; Olivier Escaffre; Michael N. Nguyen; Stefanie P. Muraro; Hana Janova; Hongming Ma; Shiqi Cao; Tomasz Kaszuba; Brian Imbiakha; Sathvik Palakurty; et al. (Proceedings of the National Academy of Sciences, 2025)
Orthoflaviviruses are a genus of arthropod-transmitted RNA viruses that infect humans and other vertebrate animals on a global scale, resulting in extensive morbidity and mortality. Among the orthoflaviviruses, tick-borne encephalitis viruses (TBEV) are an antigenic group that causes severe neurological disease in humans. However, the entry receptors for TBEV, which contribute to cell and tissue tropism, remain largely unknown. Because recent studies identified members of the low-density lipoprotein receptor (LDLR) family as possible receptors for some orthoflaviviruses and distantly related alphaviruses, we performed a targeted screen in transgenic cells expressing different LDLR members and identified LRP8 (also called ApoER2) as a candidate receptor for TBEV strains from the five different subtypes. Genetic ablation of LRP8 impaired TBEV reporter virus particle or authentic virus infection in neuronal cells. Reciprocally, complementation or ectopic expression of LRP8 increased TBEV infection. LRP8 was used as a receptor by multiple strains of TBEV and several closely related tick-borne viruses but not by the mosquito-transmitted orthoflaviviruses we tested. LRP8 bound directly to TBEV envelope proteins and promoted virus attachment to and internalization in cells through LDLR type A (LA) binding domain, which we narrowed down to LA domains 1 and 2 through functional experiments. Soluble LRP8-Fc decoy receptors neutralized TBEV in cell culture, and reduced viral infection was observed in Lrp8 −/− neuronal cells obtained from knockout mice. Our studies establish a role for LRP8 in TBEV entry and infection, which has implications for the development of soluble receptor, antibody-based, and vaccine countermeasures.